(5-x)*(3-x)*(-6-x)+18=0

Simple and best practice solution for (5-x)*(3-x)*(-6-x)+18=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5-x)*(3-x)*(-6-x)+18=0 equation:


Simplifying
(5 + -1x)(3 + -1x)(-6 + -1x) + 18 = 0

Multiply (5 + -1x) * (3 + -1x)
(5(3 + -1x) + -1x * (3 + -1x))(-6 + -1x) + 18 = 0
((3 * 5 + -1x * 5) + -1x * (3 + -1x))(-6 + -1x) + 18 = 0
((15 + -5x) + -1x * (3 + -1x))(-6 + -1x) + 18 = 0
(15 + -5x + (3 * -1x + -1x * -1x))(-6 + -1x) + 18 = 0
(15 + -5x + (-3x + 1x2))(-6 + -1x) + 18 = 0

Combine like terms: -5x + -3x = -8x
(15 + -8x + 1x2)(-6 + -1x) + 18 = 0

Multiply (15 + -8x + 1x2) * (-6 + -1x)
(15(-6 + -1x) + -8x * (-6 + -1x) + 1x2 * (-6 + -1x)) + 18 = 0
((-6 * 15 + -1x * 15) + -8x * (-6 + -1x) + 1x2 * (-6 + -1x)) + 18 = 0
((-90 + -15x) + -8x * (-6 + -1x) + 1x2 * (-6 + -1x)) + 18 = 0
(-90 + -15x + (-6 * -8x + -1x * -8x) + 1x2 * (-6 + -1x)) + 18 = 0
(-90 + -15x + (48x + 8x2) + 1x2 * (-6 + -1x)) + 18 = 0
(-90 + -15x + 48x + 8x2 + (-6 * 1x2 + -1x * 1x2)) + 18 = 0
(-90 + -15x + 48x + 8x2 + (-6x2 + -1x3)) + 18 = 0

Combine like terms: -15x + 48x = 33x
(-90 + 33x + 8x2 + -6x2 + -1x3) + 18 = 0

Combine like terms: 8x2 + -6x2 = 2x2
(-90 + 33x + 2x2 + -1x3) + 18 = 0

Reorder the terms:
-90 + 18 + 33x + 2x2 + -1x3 = 0

Combine like terms: -90 + 18 = -72
-72 + 33x + 2x2 + -1x3 = 0

Solving
-72 + 33x + 2x2 + -1x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 18x(-5)=3(6x-2) | | 5(2x+3)=24+x | | x^3+2-4x=0 | | 11+x=66 | | 15/8x=21/4(x-3) | | 5x-6=3x-x-8 | | 0.66a-0.75=0.75a | | 25+x-6+x-6=145 | | 450/50 | | 2/3(6x+3)+(x-8)=-4X+12 | | 5x+4=-5x-16 | | 1200+100c=3230+190c | | 8(3p-1)+3p= | | 2/3(9x+12)=2 | | -4=-3/4x+11 | | x-4/x*x^2+2x/x^2-16 | | 35-2/3x=13 | | 5x-7/2=5 | | 3(w+4)*4=-5(4w) | | 6p-6p=-3p+15 | | x/13+3=-2 | | 4/5a=2/3 | | 5x+2(3-x)+1=19 | | 3(w+4)*4=4w-5 | | 7(c+1)=c-2(4) | | 5-x/2=10 | | -3+2/3x=3 | | 6(1-4x)=-186 | | -26+x=3x+22 | | -6+2(2x+13)=48 | | .1x=.2(x) | | 18.08-23.37x=27/2.43x+4.2 |

Equations solver categories